2010
DOI: 10.1039/c003977b
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of ideal zeolite frameworks

Abstract: We explore the flexibility windows of the 194 presently-known zeolite frameworks. The flexibility window represents a range of densities within which an ideal zeolite framework is stress-free. Here, we consider the ideal zeolite to be an assembly of rigid corner-sharing perfect tetrahedra. The corner linkages between tetrahedra are hard-sphere oxygen atoms, which are presumed to act as freely-rotating, force-free, spherical joints. All other inter-tetrahedral forces, such as coulomb interactions, are ignored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 26 publications
7
119
1
Order By: Relevance
“…We stress that it is not obvious a priori that this idealisation should be possible at all. Indeed, we found, and subsequent research has confirmed [8,9], that this flexibility window phenomenon is almost universal in all known zeolites, with only a single known exception (framework GOO, goosecreekite), but is very uncommon in hypothetical structures. This immediately suggests that the existence of a flexibility window in a hypothetical structure is one of the missing criteria for the selection of good candidates for synthesis.…”
Section: Flexibility Windowmentioning
confidence: 89%
“…We stress that it is not obvious a priori that this idealisation should be possible at all. Indeed, we found, and subsequent research has confirmed [8,9], that this flexibility window phenomenon is almost universal in all known zeolites, with only a single known exception (framework GOO, goosecreekite), but is very uncommon in hypothetical structures. This immediately suggests that the existence of a flexibility window in a hypothetical structure is one of the missing criteria for the selection of good candidates for synthesis.…”
Section: Flexibility Windowmentioning
confidence: 89%
“…[12,42,43] It emerges that, first, actually existing real (natural or synthetic) zeolites can indeed attain ideal geometry when modelled as silica in geometric simulations. Second, this can be done over a range of densities; limits arise on expansion from extension of SiZO bonds, and in compression from steric collisions of oxygen atoms on adjacent tetrahedra ('codimeric' oxygens).…”
Section: The Flexibility Window In Zeolitesmentioning
confidence: 99%
“…Every zeolite topology exhibits a flexibility window as theoretically demonstrated by Kapko and co-workers. [21] It was observed that gas molecules with a Lennard-Jones diameter larger than the time-averaged narrow sodalite windows can diffuse through the sodalite zeolite due to framework flexibility. [22,23] Also the 5 flexibility of any bulky reaction intermediate implies a significant increase in conformational degrees of freedom that should be appropriately accounted for.…”
mentioning
confidence: 99%